Recent Fixed-Point Results for θ−Contraction Mappings in Rectangular M−Metric Spaces with Supportive Application - Mustafa Mudhesh; Hasanen A. Hammad; Habes Alsamir; Muhammad Arshad; Eskandar Ameer (Journal of Mathematics)
The goal of this manuscript is to present a new fixed-point theorem on θ−contraction mappings in the setting of rectangular M-metric spaces (RMMSs). Also, a nontrivial example to illustrate our main result has been given. Moreover, some related sequences with θ−contraction mappings have been discussed. Ultimately, our theoretical result has been implicated to study the existence and uniqueness of the solution to a nonlinear integral equation (NIE).